ANALISIS KATEGORI, FUNGSI, DAN PERAN OBJEK DALAM ARTIKEL DIGITAL: STUDI PADA ARTIKEL "TREN BARU GEN Z: JUALAN KONTEN DIGITAL, CUAN DARI PLATFORM AI - Indri Anggraeni; Wulan Amelia Putri; Siti Hanifah Kartini; Iis Lisnawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the category, function, and semantic roles of objects in the article entitled “Tren Baru Gen Z: Jualan Konten Digital, Cuan dari Platform AI”. This research employs a qualitative approach with a descriptive method. The data source is the article text, while the data consist of sentences containing objects. Data were collected using documentation techniques through reading and note-taking of relevant parts. The data analysis was conducted through identification, classification, and interpretation of objects based on their categories, functions, and roles. The results show that object categories in the article are dominated by nouns and noun phrases. In terms of function, objects serve as compl1ements to predicates in transitive sentences and act as receivers of actions. Meanwhile, based on semantic roles, objects function as patients, targets, and results. These findings indicate that the use of objects in the article plays an important role in constructing clarity of meaning and effectiveness in conveying information.